2004
DOI: 10.1079/pgr200446
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resources of oilseed Brassica and related species in Gansu Province, China

Abstract: Vavilov (1935) described China as the earliest and largest independent centre of origin of cultivated plants. Gansu Province occupies the geographic centre of China. With an area of 454,000 km2, latitudes ranging from 32°3′N to 42°57′N and elevations varying from 500 to 6200 m, the province has an extremely diverse climate and topography. Stretching 1653 km along the ancient Silk Road, Gansu also has a long history of agriculture (6000 years) and for centuries was exposed to dynamic cultural exchanges between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
(2 reference statements)
4
5
0
Order By: Relevance
“…Most accessions in our study were also taller, and height (71–120 cm) and seed weight (1.5–3.6 g/1000) were more variable, than reported by Sodani et al (1990) (57–84 cm tall, 2.3–3.9 g/1000 seeds) and Yaniv et al (1998) (1.3–1.9 g/1000 seeds). Seed oil contents in our study (25–31%) were similar to those reported by Yaniv et al (1998) (25–29%) and Mandal et al (2002) (24–30%), but lower than those reported by Sodani et al (1990) (32–36%), Yadava et al (1998) (32–41%), Gurgar et al (1999) (26–39%) and Sun et al (2004) (23–38%). Seed protein contents in our study ranged from 34–42% and were slightly higher than those reported by Sun et al (2004) (30–38%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most accessions in our study were also taller, and height (71–120 cm) and seed weight (1.5–3.6 g/1000) were more variable, than reported by Sodani et al (1990) (57–84 cm tall, 2.3–3.9 g/1000 seeds) and Yaniv et al (1998) (1.3–1.9 g/1000 seeds). Seed oil contents in our study (25–31%) were similar to those reported by Yaniv et al (1998) (25–29%) and Mandal et al (2002) (24–30%), but lower than those reported by Sodani et al (1990) (32–36%), Yadava et al (1998) (32–41%), Gurgar et al (1999) (26–39%) and Sun et al (2004) (23–38%). Seed protein contents in our study ranged from 34–42% and were slightly higher than those reported by Sun et al (2004) (30–38%).…”
Section: Discussionsupporting
confidence: 89%
“…Seed oil contents in our study (25–31%) were similar to those reported by Yaniv et al (1998) (25–29%) and Mandal et al (2002) (24–30%), but lower than those reported by Sodani et al (1990) (32–36%), Yadava et al (1998) (32–41%), Gurgar et al (1999) (26–39%) and Sun et al (2004) (23–38%). Seed protein contents in our study ranged from 34–42% and were slightly higher than those reported by Sun et al (2004) (30–38%).…”
Section: Discussionsupporting
confidence: 89%
“…Among the oleifera accessions, the Canadian spring and the European winter oilseeds clustered close to the turnip clade; this is in agreement with the descriptions of their development from turnips in the last two centuries (Gupta and Pratap 2007). Chinese winter oleifera accessions, described as an independent development (Sun et al 2004), clustered alongside Pak-choi and suggest evolution from an ancestor of modern Pak-choi, as has been described by Zhao et al (2005). The 'yellow sarson' formed its own cluster in contrast to Zhao et al (2005), where this group was found to be closely related to spring oleifera.…”
Section: Chromosomesupporting
confidence: 88%
“…Eruca species are important marginal oil crops grown on soils with reduced fertility in India, Pakistan, Canada and China, and preferred over other relative species because of their tolerance and adaptability to unfavourable environmental conditions (Ashraf, 1994; Sun et al , 1999, 2004; Prakash and Bhat, 2007; Warwick et al , 2007). Eruca lines with larger and yellow seeds, higher plant and seed yield have been reported to be available (Huang et al , 2014).…”
Section: Introductionmentioning
confidence: 99%